Shear-induced vorticity aligned flocs in a temperature responsive colloid-polymer mixture - Rel, Ryle; Terwilliger, Dennis; McGorty, Ryan (Frontiers in Physics, 2022)
Shear driven patterning is seen in many soft matter systems. We use rheology and optical microscopy to probe the structures formed when we shear a colloid-polymer mixture containing temperature-sensitive microgel particles. By increasing the temperature, we can increase the particle attraction and transition from liquid-like to gel-like behavior. And by applying shear flow to the sample as the temperature and, hence, state of the system changes, we can affect the morphology of mesoscopic colloidal clusters. We can produce gels comprised of fibrous, elongated colloid-rich clusters, or we can form more isotropic clusters. The rheology is measured and shear-induced flocculation observed for colloid-polymer systems with different cluster morphologies. At shear rates high enough to produce elongated clusters but low enough to not break clusters apart, we observe log-like flocs that are aligned with the vorticity direction and roll between the parallel plates of our rheometer.